OAUNI photometry of SN2022jli - Pereyra, Antonio (2022)
Multiband photometry of Type Ic SN2022jli (TNSTR-2022-1198, TNSCR-2022-1261) on 2022-07-01 (UT) was gathered with the OAUNI 51cm telescope (arXiv:1512.03104) at Huancayo Observatory, Peru. CCD imaging using VRI filters was performed under non-photometric conditions (seeing ~2.3") and airmass lower than 1.3. Total integration times of (60x20s=1200s) for V, R and I filters yielded: Date (UT) filter mag 2022-07-01.401 V 14.64 +/- 0.04 2022-07-01.359 R 14.52 +/- 0.05 2022-07-01.381 I 14.06 +/- 0.05. UCAC4 field stars were used for the zero point calibration. Caution must be taken in SN2022jli magnitudes for possible contamination with the host galaxy. Following GELATO and SNID classification (TNSCR-2022-1261), our measurements are aprox. 52 days after maximum brightness. The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).